Haptic system as an accessibility mechanic for hard of hearing and deaf people on video games - Menezes, Emme Costa de; Lamar, Marcus Vinicius (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This paper introduces a new haptic wearable system designed for hard-of-hearing or deaf individuals. The system’s primary objective is to create an immersive, engaging, and distinctive experience within video game contexts, by incorporating a haptic feedback interface with vibration motors. The system modular approach allows it to be applied in diverse contexts beyond gaming without needing structure changes, as it has a high-level graphic interface, able to create and edit effects regardless of its use. The obtained results are very promising to increase the immersion level of deaf people in games and other environments.